Introduction: Dispersed Minorities and Non-Territorial Autonomy. Issue 1 (1st January 2016) - Coakley, John
Abstract: The concept of non-territorial autonomy gives rise to at least two important questions: the range of functional areas over which autonomy extends, and the extent to which this autonomy is indeed non-territorial. A widely used early description significantly labelled this 'national cultural autonomy', implying that its focus is mainly on cultural matters, such as language, religion, education and family law. In many of the cases that are commonly cited, 'autonomy' may not even extend this far: its most visible expression is the existence of separate electoral registers or quotas for the various groups. Part of the dilemma lies in the difficulty of devolving substantial power on a non-territorial basis: to the extent that devolved institutions are state-like, they ideally require a defined territory. Ethnic groups, however, vary in the extent to which they are territorially concentrated, and therefore in the degree to which any autonomous arrangements for them are territorial or non-territorial. This article explores the dilemma generated by this tension between ethnic geography (pattern of ethnic settlement) and political autonomy (degree of self-rule), and introduces a set of case studies where the relationship between these two features is discussed further: the Ottoman empire and its successor states, the Habsburg monarchy, the Jewish minorities of Europe, interwar Estonia, contemporary Belgium, and two indigenous peoples, the Sámi in Norway and the Maori in New Zealand.